Clinical features and radiological findings of 67 patients with SAPHO syndrome. Issue 4 (4th July 2018) - Okuno, Hiroshi; Watanuki, Munenori; Kuwahara, Yoshiyuki; Sekiguchi, Akira; Mori, Yu; Hitachi, Shin; Miura, Keiki; Ogura, Ken; Watanabe, Mika; Hosaka, Masami; Hatori, Masahito; Itoi, Eiji; et al.
Abstract: Objectives: The purpose of this study was to facilitate the understanding of the SAPHO (Synovitis, Acne, Pustulosis, Hyperostosis, and Osteitis) syndrome by analyzing the clinical and radiological features of 67 Japanese patients with SAPHO syndrome. Methods: Sixty-seven Japanese patients (female/male: 44/23, mean age at onset: 48.5 years) were diagnosed with SAPHO syndrome from 2002 to 2013 at our hospital. Medical records and radiological imaging of these patients were retrospectively reviewed. Results: Among the 67 patients, 41 had dermatological manifestations, such as palmoplantar pustulosis, acne, and psoriasis. Initial symptom was local pain in all patients, and the most common initial site of the symptom was the anterior chest. Bacterial and fungal cultures from 20 bone biopsies were all negative. Histopathological diagnosis of the specimens was non-specific inflammation in all cases. Bone lesions were observed in 65 patients (97.0%). On the other hand, articular lesions including enthesitis were found in 31 patients (46.2%). Conclusion: SAPHO syndrome had different clinical and radiological aspects. The clinical features were not remarkable, except the dermatological manifestations and the involvement of the anterior chest. Bone lesions including hyperostosis and osteitis were found radiographically in the majority of patients with SAPHO syndrome. These are the characteristics of the SAPHO syndrome, with the exclusion of other bone diseases.